Acute and chronic effects of Cr(VI) on Hypsiboas pulchellus embryos and tadpoles - Natale, Guillermo Sebastián (2006)
In the last few years there has been great concern about declines in the abundance of several species of amphibians around the world. Among amphibians, anurans have a biphasic life cycle, with aquatic tadpoles and generally terrestrial adults, and they have an extremely permeable skin, making them excellent indicators of the health of the environment. A number of different causes have been suggested for the global decline of anurans, the pollution of their habitat by chemical stressors being considered one of the major factors. Among chemical stressors, heavy metals are known for their high toxicity at very low concentrations. This study assessed short- (96 h, 'acute') and long-term (1272 h, 'chronic') exposure to Cr(VI) at lethal (3 to 90 mg l-1) and sublethal concentrations (0.001 to 12 mg l-1) on Hypsiboas pulchellus (previously called Hyla pulchella; see Faivovich et al. 2005) tadpoles (Fam. Hylidae) from central eastern Argentina. Fertilized eggs collected from a clean pond near La Plata (Buenos Aires Province) were used for acute and chronic toxicity testing. Assays were done under controlled laboratory conditions. Results of chronic exposure were used to assess the effect of factors such as toxicant concentration and age of organisms at the beginning of exposure on the response variables (growth, development and survival until metamorphosis). Results indicated a higher sensitivity to Cr(VI) of individuals first exposed as tadpoles than those first exposed as embryos during acute and chronic exposure. Exposure to the highest sublethal concentrations (6 to 12 mg l-1) of the toxicant showed early inhibitory effects on growth of all treated organisms compensated at longer exposure periods with an increase in the growth rate compared to the control groups.